(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Preparation of economic facilities for sustainable operation in emergency situations consists in carrying out a set of measures of an organizational, technical, technological, production, economic, scientific, educational and other nature aimed at preventing emergency situations, reducing damage from them, maintaining the maximum possible level of performance of production or other target functions of the object. This, in turn, predetermines the need for deep scientific study, collecting information on regulatory documents, performing a system analysis, studying experience and, on the basis of the resulting problems, develop a unified system of regulatory documents, as well as introduce practical implementation in our country.